Initiating HERMÓPOLIS Collaborative Design: Local Definitions for Building a Global Smart City Platform to Improve the Quality of Life of the Elderly - Víctor Manuel Padrón Nápoles; José Luis Esteban Penelas; Esther Pizarro Juanas; Juan Diego López-Arquillo; Esther Delgado-Pérez; Alberto Bellido-Esteban; Rafael Muñoz Gil; Olalla García Pérez; Patricio Martínez García; Ignacio Loscertales; Silvia Álvarez Menéndez; Mariana Bernice Arteaga Orozco (Urban Science)
Smart furniture (smart cities) can provide publicity, mobility services and local government communication, among many other services; however, its use for improving the quality of life of the elderly (extended IP-spaces concept) can be further researched. This paper describes the first step in a collaborative design of a smart city platform based on this concept. This design requires a layered design, as it includes architectonic, artistic, technological and social aspects. Participatory design (PD) and participatory action research (PAR) methodologies were selected to include the elderly in the design to ensure the acceptance and usability of the system. During this specific design process, three groups of elderly people from three geographic points of Spain were recruited. PD was applied to capture the users’ preferences and general specifications regarding the architectonic aspect of the project, while PAR was used to capture these groups’ quality-of-life needs, determine the initial acceptance of the project and define the initial activities to be realized for mitigating the detected needs. The application of these qualitative methodologies should produce a user-centric, valuable but local (specific) design. As more groups and towns will be involved, the new local designs will build a bigger set of validated solutions that potentially could be customized and reused for other contexts.